Nitrogen in Atmospheric Wet Depositions Over the East Indian Ocean and West Pacific Ocean: Spatial Variability, Source Identification, and Potential Influences - Jiang, Shan; Jin, Jie; Jiang, Shuo; Wu, Ying; Wang, Jianing; Chen, Ju; Zhang, Zhenqiu; Liu, Sumei; Chang, Yan; Wang, Lingyan; Zhang, Jing (Frontiers in Marine Science, 2021)
Atmospheric deposition is the dominant pathway for the loading of exogenous nitrogen (N) to open ocean. Here, rainwater samples were collected from 31 stations in the equatorial East Indian Ocean (EIO) and West Pacific Ocean (WPO) to explore spatial variability of N species, potential sources and related ecological influences. Among two oceans, nitrate (NO3-) and ammonium (NH4+) were main components in the rainwater N inventory. NO3- concentrations varied from 0.19 to 100.5 μM, while NH4+ concentrations ranged from 0.54 to 110.6 μM. Among all stations, low concentrations of NO3- and NH4+ appeared in the remote ocean, while high concentrations were observed at the stations near the Malacca Strait and the New Guinea, coupled with an enhancement of non-seasalt major ions, e.g. calcium ions (Ca2+) and sulfate (SO42-), revealing the influence from coastal human activities, such as coal and gasoline combustion. In the remote ocean, δ15N-NH4+ ranged from -5.7‰ to -9.3‰, while it dropped to -15.5‰ near coasts. A logarithmic decay between δ15N-NH4+ and NH4+ concentration in rainwater samples was obtained, suggesting a shift from natural source (seawater emission) in oceanic precipitation events to anthropogenic source (chemical fertilizer volatilization and vehicle exhaust) in coastal rainwaters. δ15N-NO3- in the remote ocean varied between -1.7‰ and 0.4‰ with low levels found in the WPO, likely related to the ascending air flow driven by the Walker Circulation. In coastal oceans, δ15N-NO3- ranged from 1.5‰ to 3.5‰. The linkage between δ15N-NO3- and NO3- concentration varied in two oceans, resulting from difference in biological and fossil fuel combustion contributions. Compared to ocean surface water, N in the rainwater was markedly enriched, suggesting that N from atmospheric wet depositions could rapidly enhance the dissolved nitrogen availability in ocean surface water. However, the N redundancy according to the Redfield-Brzezinski ratio (N: Si: P=16:16:1) in the rainwater might benefit the growth of N-preference phytoplankton species and microbes. As the first study on N concentrations, sources and stoichiometry balance in rainwater over the equatorial WPO and EIO, the results could be a support to the global N budget estimation and oceanic primary production modeling.